KONFLIK SOSIAL-EKONOMI DALAM NOVELBATAS ANTARA KEINGINAN DAN KENYATAAN KARYA AKMAL NASERY BASRAL - NFN Musfeptial (Kantor Bahasa Sulawesi Tenggara, 2017)
This research entitled ”Socio-Economic Conflict in Novel Batas Antara Keinginan dan Kenyataanby Akmal Nasery Basral”. The border regions of the country, such as Entikong in West Kalimantan, are important areas because there are cross-border boundary post which is the entrance of people from Indonesia and Malaysia. In addition, there are also dozens of paths that become the entrance to the country of Malaysia. Banayak conflicts that occur in national borders, such as social and economic conflicts. This is also the reason why research on this novel is interesting and important to do. This study aims to obtain a complete description of the social and economic conflicts of the novel. The theory used in this kajain is the theory of sociology of literature This research is a qualitative research with descriptive research method of analysis. Data analysis shows the social and economic conflicts of this novel. The social conflict in this novel is seen from the conflict between Otiq and the people in Ponti Tembawang. This social conflict is rooted in the business of smuggling labor abroad. Meanwhile, the economic conflict. Rooted in the control of trade on the border.